Arthroscopic Management of the Hamate Proximal Pole Arthrosis. Issue 11 (21st November 2022) - Ali, Barkat; Ozyurekoglu, Tuna
Abstract : Background: Arthrosis of the proximal pole of the hamate is a peculiar cause of ulnar-sided wrist pain. We present clinical, functional, and patient-reported outcomes of arthroscopic management. Methods: In this retrospective study, all patients with arthrosis of the proximal pole of the hamate encountered in a 10-year period treated with arthroscopy were reviewed. Patient demographics, arthroscopic details, associated injuries, and procedures were reviewed. Functional and patient-reported clinical outcomes after arthroscopic osteochondroplasty were analyzed. Results: An analysis of 39 patients who underwent arthroscopic osteochondroplasty showed a type II lunate prevalence of 87.2%. On wrist arthroscopy, a triangular fibrocartilaginous complex tear was the most common diagnosis (64.1%), followed by scapholunate ligament tear (61.5%) and lunotriquetral ligament tear (35.9%). All patients were managed arthroscopically with 100% procedural success. Average follow-up of 42.8 ± 37.7 months showed statistically significant improvements in the visual analog score and Mayo wrist score postoperatively ( P < 0.01). Three patients (7.7%) failed the procedure at a mean of 23 ± 31.4 months. Risk factors for salvage operations were nondominant wrist involvement 100% ( P = 0.04), lunotriquetral ligament injury 100% ( P = 0.04), the absence of triangular fibrocartilaginous complex injury 100% ( P = 0.04), and the presence of scapholunate advanced collapse 100% ( P < 0.01). Conclusions: Wrist arthroscopy is valuable for accurately diagnosing and treating hamate arthrosis and identifying a wide variety of pathologies associated. This study showed arthroscopic osteochondroplasty produced satisfactory clinical results. Furthermore, the presence of scapholunate advanced collapse wrist offers its prognostic value in determining treatment failure.